Anti-convulsant Action and Attenuation of Oxidative Stress by Citrus limon Peel Extracts in PTZ and MES Induced Convulsion in Albino Rats - Sahu, Dipika R.; Chowdhury, Bimalendu; Sahoo, Biswa M. (Central Nervous System Agents in Medicinal Chemistry, 2020)
Background: Citrus limon a small evergreen plant belongs to the family Rutaceae. These species are extensively cultivated throughout the world because of their multiple health benefits for humans and their applications in the pharmaceutical and food industries. Various studies were conducted using their plant parts (fruits, flowers, peels, leaves, blossoms) but the studies on peel extracts are very limited. However, the anticonvulsant activity of peels has not been studied yet. Objective: The main goal of this study is to appraise the anticonvulsant effect stimulated by the antioxidant property of hydroalcoholic extracts of Citrus limon (HAECL) peels in various animal models. Methods: The anticonvulsant and in vivo antioxidant activity of HAECL peels was observed by Maximal electric shock (MES) model, pentylenetetrazole (PTZ) induced clonic convulsion model and PTZ induced kindling test. The extract was administered to test groups at doses of 200, 400 and 600 mg/kg. orally in PTZ and MES methods. The highest dose of extract was given to the test grouped animals in case of a kindling test. After completion of the time period of kindling, the brains of all grouped animals were isolated and subjected to analyse oxidative stress parameters such as malondialdehyde (MDA), superoxide dismutase (SOD), catalase (CAT) and glutathione (GSH) biochemically to investigate the antioxidant profile of the plant. Results: HAECL peels at doses of 400 and 600 mg/kg significantly (p<0.01) delayed the onset, decreased the duration of myoclonic spasm in PTZ induced seizure model and also significantly (p<0.01) decreased the duration of hind limb tonic extension (HLTE) as well as significantly (p<0.05) increased the postictal depression (PID) in MES model compared to control. In the PTZinduced kindling model, the malondialdehyde (MDA) level was elevated with a diminished level of SOD, CAT, GSH compared to the control group but pretreatment with HAECL at the highest dose reduced the MDA level and refined SOD, CAT and GSH status effectively. Conclusion: From the above investigation, it was concluded that HAECL could produce significant anticonvulsant activity and also attenuate oxidative stress-induced during a seizure.
Keywords: Hydroalcoholic extracts